Traditional Environmental Knowledge in a Changing Environment : Vuntut Gwitchin Observations of Change in the Yukon Territory - Consiglio, Erin M (Anthropologica, 2024)
Scientists, resource managers and developers increasingly seek out Traditional or Indigenous Knowledge to deepen their understanding of the environment. Yet, even as the value of this knowledge is recognized, misperceptions remain; Traditional Knowledge is still often seen as something static, unchanged from one generation to the next rather than as something flexible and adaptive. Ethnographic research with the Vuntut Gwitchin First Nation challenges these perceptions. Their observations of contemporary environmental change in the western Canadian Arctic are becoming part of their Traditional Knowledge, proving that this system of knowledge is resilient and will continue even as the environment becomes ever more unpredictable. Les scientifiques, les gestionnaires de ressources et les promoteurs recherchent de plus en plus les connaissances traditionnelles ou autochtones pour approfondir leur compréhension de l’environnement. Pourtant, des perceptions erronées subsistent bien que la valeur de ces connaissances soit reconnue : les connaissances traditionnelles sont encore souvent perçues comme statiques, immuables d’une génération à l’autre, plutôt que flexibles et adaptables. Les recherches ethnographiques menées auprès de la Première Nation Gwitchin Vuntut remettent en question ces perceptions. Les observations des changements environnementaux contemporains dans l’ouest de l’Arctique canadien font désormais partie de leurs savoirs traditionnels, prouvant ainsi que ce système de connaissances est résistant et qu’il se maintiendra même si l’environnement devient de plus en plus imprévisible.